2018
DOI: 10.1017/s0021859617000958
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary protein content on performance, feed efficiency and carcass traits of feedlot Nellore and Angus × Nellore cross cattle at different growth stages

Abstract: An experiment was conducted to evaluate whether a reduction in dietary crude protein (CP) and genotype affects animal performance, feed efficiency and carcass traits of beef cattle at different stages of the feedlot. Twenty-two Nellore and 22 crossbred F1 Angus × Nellore (Nellore: 8 months, initial body weight (iBW) = 212.7 kg; Crossbred: 8 months, iBW = 226.1 kg) were used in this experiment. The experiment was conducted in a complete randomized design with six replicates, in a 2 × 3 factorial design. The fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 20 publications
2
12
0
Order By: Relevance
“…At the end of this period, or during the finishing phase (56 d), dietary CP content could be reduced to 100 g CP/kg DM without affecting animal performance during this phase. In agreement with Amaral et al (2018) , this study shows that reducing CP from 145 to 105 g CP/kg DM or oscillating CP supply did not affect animal performance and carcass characteristics of growing Nellore bulls.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…At the end of this period, or during the finishing phase (56 d), dietary CP content could be reduced to 100 g CP/kg DM without affecting animal performance during this phase. In agreement with Amaral et al (2018) , this study shows that reducing CP from 145 to 105 g CP/kg DM or oscillating CP supply did not affect animal performance and carcass characteristics of growing Nellore bulls.…”
Section: Resultssupporting
confidence: 89%
“…Data from the literature suggest that for growing animals, dietary CP content influences weight gain ( Winchester et al, 1957 ), and an optimal CP for beef cattle is approximately 13% over the grow out period ( Gleghorn et al, 2004 ) and is greater during early feeding and less during the finishing phase, as cattle approach final weight ( Todd et al, 2008 ). Amaral et al (2018) developed a study with Nellore and crossbred Nellore x Angus bulls divided into three groups receiving diets with 100, 120, and 140 g CP/kg DM. This author observed that calves that were weaned and thereafter finished in feedlot should receive diets with CP content of approximately 120 g CP/kg DM during the initial growing phase (84 d).…”
Section: Resultsmentioning
confidence: 99%
“…Concurrently, as dietary protein concentration and protein deposition are increased, the rate of fat deposition decreases resulting in accrual of an increased amount of lean in the body (Cooke et al, 1972). More recently, it was reported that as dietary protein concentrations increased (100, 120, or 140 g/kg DM), there was also a linear increase in ADG of backgrounding cattle (Amaral et al, 2018). Additionally, feeding metabolizable protein at 85%, 100%, or 115% of the daily requirements also resulted in a linear increase in the weight gain of preconditioning beef steers (Moriel et al, 2015).…”
Section: Effects Of Nutrition On Skeletal Muscle Growthmentioning
confidence: 99%
“…Although a complete review of dietary protein and AA concentrations is beyond the scope of this review, it is important to understand that adequate dietary protein nutrition is important in ensuring that optimal skeletal muscle growth occurs in livestock species. Most of the research analyzing specific AAs has been completed using human, rodent, and porcine models, but recent research does indicate that dietary protein concentration is related to gross, phenotypic changes relating to growth of skeletal muscle in cattle (Moriel et al, 2015;Hales et al, 2016;Amaral et al, 2018). To date, most of the research analyzing the impacts of nutrient status on growth of skeletal muscle in livestock has not focused on SC specifically, but rather on phenotypic changes relating to overall skeletal muscle growth.…”
Section: Effects Of Nutrition On Skeletal Muscle Growthmentioning
confidence: 99%
“…Protein supplementation to ruminants often increases growth performance, which makes protein a limiting nutrient for production ( Medeiros and Marino, 2015 ). However, excessive use of protein in finishing diets leads to economic losses and environmental implications due to excess of nitrogen excretion ( Amaral et al , 2018 ). In addition, N excretion in ruminants is not only related to N intake but also microbial efficiency that influences metabolizable protein (MP) supply ( Niu et al , 2016 ).…”
Section: Introductionmentioning
confidence: 99%